Biosynthesis, characterization and anti-dengue vector activity of silver nanoparticles prepared from Azadirachta indica and Citrullus colocynthis. Issue 9 (9th September 2020) - Rasool, Shafqat; Raza, Muhammad Akram; Manzoor, Farkhanda; Kanwal, Zakia; Riaz, Saira; Iqbal, Muhammad Javaid; Naseem, Shahzad
Abstract : We report here biosynthesis of silver nanoparticles (AgNPs) using aqueous extracts of (i) Azadirachta indica leaves and (ii) Citrullus colocynthis fruit and their larvicidal activity against Aedes aegypti. The UV–Vis spectroscopy absorption peaks occurred in the range of 412–416 nm for A. indica AgNPs and 416–431 nm for C. colocynthis AgNPs indicating the silver nature of prepared colloidal samples. The scanning electron microscopy examination revealed the spherical morphology of both types of NPs with average size of 17 ± 4 nm ( A. indica AgNPs) and 26 ± 5 nm ( C. colocynthis AgNPs). The X-ray diffraction pattern confirmed the face-centred cubic (FCC) structure with crystallite size of 11 ± 1 nm ( A. indica AgNPs) and 15 ± 1 nm ( C. colocynthis AgNPs) while characteristic peaks appearing in Fourier transform infrared spectroscopy analysis indicated the attachment of different biomolecules on AgNPs. The larvicidal activity at different concentrations of synthesized AgNPs (1–20 mg l −1 ) and extracts (0.5–1.5%) against Aedes aegypti was examined for 24 h. A concentration-dependent larvicidal potential of both types of AgNPs was observed. The LC50 values were found to be 0.3 and 1.25 mg l −1 for C. colocynthis AgNPs and A. indica AgNPs, respectively. However, both extracts did not exhibit any notable larvicidal activity.